Medical management and rehabilitation in posttraumatic common peroneal nerve palsy (Balneo and PRM Research Journal, 2022)
Introduction. The common peroneal nerve and the tibial nerve are the two major components into which the sciatic nerve divides. The severity of common peroneal nerve damage depends on the aetiopathogenic mechanism and the place of injury. The peroneal ram of the sciatic nerve injury is the most common cause of mononeuropathy of the lower limb which can cause a significant disability if is not properly diagnosed and treated. Material and method. We present the case of a 40-year-old patient who suffered a polytrauma by road accident resulting in left trochanteric-diaphyseal femoral comminuted open fracture, lacerated wound on the posterolateral middle third of the left thigh, left sacral wing fracture without displacement, left L1, L2, L3 transverse apophyseal fractures and splenic laceration, treated surgically and orthopedically. The patient was admitted to the Medical Reabilitation Department of Sibiu for left leg motor deficit, mechanical pain and functional deficit of the left hip and ankle, gait disorders. Complex rehabilitation treatment was initiated 3 months after the accident. Results and discussion. Common peroneal nerve palsy was confirmed following neurological consultation the day after admission to Orthopaedics-Traumatology Department of Sibiu where continuous extension-traction was performed in order to relax the fracture and subsequent osteosynthesis surgery of the femur fracture. The presence of a deep and lacerating wound on the posterolateral left thigh caused the nerve injury. The coagulase-negative Staphylococcus aureus overinfection of the wound required secondary suturing and subsequently led to fibrous scar formation, adversely affecting the post-injury repair of the common fibular nerve. Conclusions. In patients with posttraumatic common peroneal nerve palsy, early diagnosis and appropriate treatment, including medical rehabilitation, are essential. Medical rehabilitation should be continued on a sustained basis because nerve regeneration occurs slowly. The prognosis mainly depends on the severity of the initial nerve injury.